The use of polymerase chain reaction (PCR) to confirm presence of selected pathogenic bacteria along milk value chain in Tanga region - Shija, F.; Misinzo, G.; Nonga, H.; Kurwijila, Lusato R.; Roesel, Kristina; Grace, Delia (2013)
BACKGROUND Despite the fact that foods of animal source are a minor constituent in most diets, they are responsible for incidents of food-borne illness; dairy products being implicated. Up to 90% of all dairy – related diseases are due to pathogenic bacteria found in milk. Emergence of new milk-borne bacterial pathogens with more serious challenges such as E.coli O157:H7 has been reported.